Identification of Sp1 as a Transcription Activator to Regulate Fibroblast Growth Factor 21 Gene Expression. (29th March 2017) - Chen, Shuqin; Li, Huating; Zhang, Jing; Jiang, Shan; Zhang, Mingliang; Xu, Yilan; Dong, Kun; Yang, Ying; Fang, Qichen; Jia, Weiping
Abstract : Fibroblast growth factor 21 (FGF21) is a metabolic hormone with multiple beneficial effects on lipid and glucose homeostasis. Previous study demonstrated that FGF21 might be one of the Sp1 target genes. However, the transcriptional role of Sp1 on FGF21 in adipose tissue and liver has not been reported. In this study, we found that the proximal promoter of mouse FGF21 is located between −63 and −20 containing two putative Sp1-binding sites. Sp1 is a mammalian transcription factor involved in the regulation of many genes during physiological and pathological processes. Our study showed that overexpression of Sp1 or suppressing Sp1 expression resulted in increased or reduced FGF21 promoter activity, respectively. Mutation analysis demonstrated that the Sp1-binding site located between −46 and −38 plays a primary role in transcription of FGF21. Electrophoretic mobility shift assay and chromatin immunoprecipitation analysis indicated that Sp1 specifically bound to this region. Furthermore, the binding activity of Sp1 was significantly increased in adipose tissues of HFD-induced obese mouse and liver of DEN-treated mouse. Thus, our results demonstrate that Sp1 positively regulates the basal transcription of FGF21 in the liver and adipose tissue and contributes to the obesity-induced FGF21 upregulation in mouse adipose tissue and hepatic FGF21 upregulation in hepatocarcinogenesis.